Auditory involvement in Behcet's disease: relationship with demographic, clinical, and therapeutic characteristics. Issue 2 (February 2017) - Sota, Jurgen; Vitale, Antonio; Orlando, Ida; Lopalco, Giuseppe; Franceschini, Rossella; Fabiani, Claudia; Galeazzi, Mauro; Emmi, Giacomo; Gentileschi, Stefano; Iannone, Florenzo; Frediani, Bruno; Cantarini, Luca
Abstract The study objective was to evaluate the occurrence of sensorineural hearing loss (SNHL) in patients with Behcet's disease (BD), looking at potential correlations with specific demographic, clinical, and therapeutic features. Forty-four consecutive patients (15 males, 29 females) fulfilling the International Study Group (ISG) and/or the International Criteria for Behçet's Disease (ICBD) were enrolled. The endpoints of the study consisted in identifying a deflection of at least 25 dB on pure-tone audiometry and performing statistical analysis to evaluate demographic, clinical, or therapeutic differences between patients with and without SNHL. Our patients showed a mean age ± SD of 45.43 ± 14.05 years; a mean age at disease onset ± SD of 31.54 ± 15.53 years; a disease duration ± SD of 13.89 ± 9.15 years. SNHL was highlighted in 28 (63 %) patients representing the fourth most frequent clinical manifestation in our group of patients. Otologic involvement was significantly more frequent among subjects fulfilling ISG criteria than in patients fulfilling ICBD criteria (p = 0.04). Regarding correlations with BD manifestations, SNHL was significantly associated with cutaneous plus articular involvement (p = 0.013). Conversely, detached analysis of articular and skin manifestations led to no significant differences (p = 0.085 andp = 0.067). No further significant correlations were found between SNHL and BD clinical features or previous or concomitant treatments. Hearing loss was the fourth most common clinical feature in our patients and probably represents an underrated aspect of BD. Hearing impairment was significantly associated with cutaneous plus articular involvement, suggesting the importance of an otologic evaluation in such patients.